Relationship between cannabis use and psychiatric disorders in patients admitted at Dr George Mukhari Hospital Psychiatric Unit - Modisane, L. N. (University of Limpopo (Medunsa Campus), 2010)
BACKGROUND Cannabis is the commonly used illicit drug of choice in South Africa and throughout the world. The majority of individuals who use cannabis do not report adverse reactions to it, however a minority of heavy users will develop problems. A substantial number of patients admitted at our psychiatry unit seem to be using cannabis. AIMS The aim of the study was to assess the relationship between cannabis use in psychiatric disorders in patients admitted in George Mukhari Hospital Psychiatry Unit, to determine the pattern of cannabis use, to identify the common psychiatric disorders in patients using cannabis, to determine the socio-economic factors that may lead to cannabis use. METHODS A total of 75 participants admitted at Doctor George Mukhari hospital and diagnosed with psychiatric disorders according to the diagnostic and statistical manual of mental disorders fourth edition text revised were interviewed using a structured questionnaire and had urine specimens collected for analysis. Out of 75 participants a control group of 34 participants who tested negative for urinary cannabinoids were interviewed. The participants had signed a written informed consent in their language of preference. The study had been approved by the Research Ethics and Publications Committee of the University of Limpopo (Medunsa Campus).Data was analysed with the help of the statistician and reported on graphs, pie-charts and tables. RESULTS 16(39%) of participants who tested positive were diagnosed with schizophrenia, 7 (17%) of those who tested positive were diagnosed with cannabis induced psychotic disorder, 5(12%) of those tested positive were diagnosed with psychosis due to GMC (HIV) and 6(15%) were diagnosed with psychosis due GMC (epilepsy). 8(24%) of those who tested negative were diagnosed with schizophrenia, 15(44%) of those tested negative were diagnosed with cannabis induced psychotic disorder, 2(6%) were diagnosed with psychosis due to GMC (HIV) and to 2(6%) of those who tested negative were diagnosed with psychosis due to GMC (epilepsy). Majority 24 (32%) smoked cannabis using pipes 4-5 times, 19 (25%) used zols 4-5 times, 12(16%) used pipes 2-3 times, 11(14%) used 1 zol in the 30 days prior to the interview. Most of the participants were of low socio-economic status and had started using cannabis early in their lives. CONCLUSION Cannabis use is related to a number of psychiatric disorders in patients admitted at Dr George Mukhari Hospital. Schizophrenia, cannabis induced psychotic disorder, psychosis due to GMC (HIV), psychosis due to epilepsy were the commonest identified disorders.
Thesis (M Med (Psychiatry))--University of Limpopo, 2010.
Keywords: Cannabis; Cannibalism